(untitled) (Revista Cocar, 2025)
In this article, we narratively explore the challenges and possibilities we faced while teaching and supervising undergraduate and graduate students remotely during the COVID-19 pandemic in two Brazilian public universities. By engaging in a narrative inquiry, we share stories of our personal and professional experiences lived in the context of distance education. Amid ongoing tensions and uncertainties, we discuss how remote teaching, while marked by challenges, also enabled meaningful digital interactions and opened space for empathy, inclusion, and pedagogical innovation. We also examine institutional limitations and social-technical barriers, while recognizing the transformative potential of online education. By telling and retelling our stories, we deepened our understanding of ourselves, our students, and our institutions. Keywords: Teacher education; Remote teaching; Narrative inquiry. Resumo Neste artigo, exploramos narrativamente os desafios e as possibilidades que enfrentamos ao ensinar e orientar estudantes de graduação e pós-graduação remotamente durante a pandemia de covid-19 em duas universidades públicas brasileiras. Desenvolvendo uma pesquisa narrativa, compartilhamos histórias de nossas experiências pessoais e profissionais vividas no contexto da educação a distância. Em meio a tensões e incertezas contínuas, discutimos como o ensino remoto, embora marcado por desafios, também possibilitou interações digitais significativas e abriu espaço para a empatia, a inclusão e a inovação pedagógica. Também examinamos limitações institucionais e barreiras sociotécnicas, ao mesmo tempo em que reconhecemos o potencial transformador da educação online. Ao contar e recontar nossas histórias, aprofundamos nossa compreensão sobre nós mesmas, nossas instituições e estudantes. Palavras-chave: Formação docente; Ensino remoto; Pesquisa narrativa.